2010
DOI: 10.1158/1078-0432.ccr-10-0483
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Promotes Ovarian Cancer Growth through Dysregulated Cell Cycle, Diminished Apoptosis, and Enhanced Angiogenesis

Abstract: Purpose: Chemokine receptor CXCR2 is associated with malignancy in several cancer models; however, the mechanisms involved in CXCR2-mediated tumor growth remain elusive. Here, we investigated the role of CXCR2 in human ovarian cancer.Experimental Design: CXCR2 expression was silenced by stable small hairpin RNA in ovarian cancer cell lines T29Gro-1, T29H, and SKOV3. Western blotting, immunofluorescence, enzyme-linked immunosorbent assay, flow cytometry, electrophoretic mobility shift assay, and mouse assay wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
153
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 50 publications
14
153
1
1
Order By: Relevance
“…The role of IL-8 and CXCR2 in tumor development and progression has been well documented in a wide range of cancer types (8,(27)(28)(29)(30)(31). Our previous data and others have shown that the IL-8/CXCR2 pathway plays a key role in mediating colorectal cancer development (11,14,15,32).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The role of IL-8 and CXCR2 in tumor development and progression has been well documented in a wide range of cancer types (8,(27)(28)(29)(30)(31). Our previous data and others have shown that the IL-8/CXCR2 pathway plays a key role in mediating colorectal cancer development (11,14,15,32).…”
Section: Discussionmentioning
confidence: 80%
“…IL-8 expression is upregulated by hypoxia, cytokines, and other environmental stresses, which are mediated by transcription factors, including NF-kB and AP-1 (6,7). The upregulation of CXCR2 has also been correlated with promotion of tumorigenesis and angiogenesis in lung, melanoma, and ovarian cancers (8)(9)(10). Previous studies by our group and others have shown that IL-8 and its receptor CXCR2 are significantly upregulated in the tumor and its microenvironment in colorectal cancer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 92%
“…Upregulation of CXCR2 mediates IL-8-induced invasive and migratory phenotype of melanoma cells (24) and is associated with a more aggressive phenotype in hepatocellular (27), gastric (28) and colorectal (29) carcinoma. The mechanisms by which CXCR2 facilitates transformation and migratory responses evoked during oncogenesis are, at least partially, due to manipulation of a comprehensive signaling network comprising phosphati dylinositol 3-kinase/protein kinase B (AKT), nuclear factor κB, Ras, mitogen-activated protein kinase (MAPK) and JAK/STAT-3 (28,(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, elevated PUMA expression, either alone or in combination with chemotherapy or irradiation, induced profound toxicity to a variety of cancer cells, including lung, head and neck, esophagus and breast cancer cells (24)(25)(26)(27). More recently, several studies have shown that PUMA is involved in chemosensitivity via regulating apoptotic signaling pathways (28)(29)(30). However, the role of PUMA in the therapeutic responses of ovarian cancer cells to platinum-based anticancer drugs remains unclear.…”
Section: Introductionmentioning
confidence: 99%